CXCR4 promotes gefitinib resistance of Huh7 cells by activating the c‐Met signaling pathway - Dali Zhao; Zhiqiang Yang; Chen Chen; Zhipeng Zhang; Yangsheng Yu; Zhituo Li (FEBS Open Bio)
C‐X‐C chemokine receptor type 4 (CXCR4) expression is associated with poor prognosis of hepatocellular carcinoma (HCC). The aim of this study was to explore the biological role of CXCR4 in gefitinib resistance of HCC. Compared with a normal, non‐gefitinib‐resistant, human HCC cell line (Huh7), CXCR4 mRNA and protein were highly expressed in gefitinib‐resistant Huh7 cells (Huh7‐R). Cell proliferation was decreased, and apoptosis was enhanced in Huh7 cells in the presence of gefitinib. These influences conferred by gefitinib treatment on proliferation and apoptosis of Huh7 cells were abolished by CXCR4 overexpression. CXCR4 knockdown reduced the proliferation ability of HuH‐7R cells after gefitinib treatment. Importantly, CXCR4 overexpression had no influence on caveolin 1 (Cav‐1) expression; similarly, Cav‐1 silencing did not cause a substantive change in CXCR4 expression. However, CXCR4 activated Cav‐1, c‐Met, and Raf‐1 in Huh7 cells, whereas Cav‐1 silencing repressed the expression of Raf‐1 and phosphorylated c‐Met in Huh7 cells. CXCR4 overexpression promoted proliferation and repressed apoptosis in gefitinib‐treated Huh7 cells, which was partly rescued by PHA‐665752 (a c‐Met inhibitor) treatment or c‐Met deficiency. Finally, we constructed a tumor xenograft model to determine the influence of CXCR4 overexpression on tumor growth of HCC. CXCR4 overexpression accelerated tumor growth of HCC, which was abrogated by c‐Met deficiency. These findings demonstrate that CXCR4 overexpression activates c‐Met via the Cav‐1 signaling pathway, thereby promoting gefitinib resistance of Huh7 cells. Thus, this study highlights novel insights into the mechanism of gefitinib resistance of HCC and CXCR4 may become a potential target for HCC treatment.